Literature Study: Learning Methods And Models To Improve Elementary School Students' Football Learning Outcomes - Arham Syahban; Hasniah Hasniah (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research is a literature study with a literature review that attempts to describe learning methods and models that can improve football learning outcomes at the elementary school level. In this research, the author collected various references in the form of journals that were relevant to the problem topic being researched using the Harzing: Publish or Perish (PoP) database. The research results found 22 journals published in 2018 - 2023 and there were 12 types of learning methods used that were effective in improving elementary school students' football learning outcomes. The most widely used learning methods and models are the play method and the Student Team-Achievement Division (STAD) type cooperative learning model. Meanwhile, the basic football techniques that are most studied are basic passing and dribbling techniques.